Burden of tinea capitis among children in Africa: protocol for a systematic review and meta-analysis of observational studies, 1990–2020 - Felix Bongomin; Ronald Olum; Lauryn Nsenga; Joseph Baruch Baluku (BMJ Open)
Introduction Tinea capitis is the most common form of dermatophytosis among children, contributing significantly to the global burden of skin and hair infections. However, an accurate account of its burden in Africa, where most cases are thought to occur, is lacking. We aim to systematically evaluate the burden, aetiology and epidemiological trend of tinea capitis among children over a 30-year period in Africa.Methods and analysis A systematic review will be conducted using Embase, PubMed, African Journals Online, Web of Science and the Cochrane Library of Systematic Review. These resources will be used to identify studies published between 1990 and December 2020, which report the prevalence, aetiology and trend of tinea capitis among children younger than 18 years in Africa. Articles in English and French will be considered. Two independent reviewers will screen the articles for eligibility, and any discrepancies will be resolved by discussion and consensus between the authors. Methodological quality of all studies will be assessed and critically appraised. We will perform a metaregression to assess the impact of study characteristics on heterogeneity and also to correct the meta-analytical estimates for biases. A qualitative synthesis will be performed, and STATA V.16.0 software will be used to estimate the pooled prevalence and aetiology of tinea capitis. The Mann-Kendall trend test will be use to evaluate the trend in the prevalence of tinea capitis over the study period.Ethics and dissemination Ethical approval from an institutional review board or research ethics committee is not required for this systematic review and meta-analysis. The results will be published in a peer-reviewed journal and presented in conferences.